Novel biotechnological substances in higher plants - Azizullah, Azizullah; Taimur, Nadia; Häder, Donat-Peter (Natural Bioactive Compounds. Technological Advancements, 2021)
Green plants are a natural source of many different products that we use directly or indirectly in our everyday life. Plant-derived products are also used as templates in the designing and synthesis of many synthetic compounds. Although in the present synthetic era many products of everyday use available in the market are produced synthetically, the importance of natural products derived from plants cannot be reduced and the interest in this domain is increasing day by day. In this chapter, we discuss the novel biological products derived from plants for applications in drugs and medicines, fragrances, pesticides, repellents, photosensitizers, and tannins.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Antioxidats; Fragrances; Higher plants; Pesticides; Repellents